2017
DOI: 10.3201/eid2302.161292
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of US Travelers to Zika Virus–Affected Countries in the Americas, March 2015–October 2016

Abstract: Zika virus has recently been introduced to the Americas and is spreading rapidly. We evaluated the characteristics of US travelers to Zika virus–affected countries who were seen at Global TravEpiNet sites during March 2015–October 2016. Nearly three quarters of travelers were men or women of reproductive age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
2
1
0
Order By: Relevance
“…The demographic data of cases reported in this study were very similar to those reported among US travellers (60% women) [ 9 ]: considering the risk of severe pregnancy outcomes [ 10 ], it is expected that women of reproductive age, and particularly pregnant women, are more frequently tested. In our study, approximately 16% of infected women of reproductive age were pregnant, which is suggestive of increased testing in pregnant women.…”
Section: Discussionsupporting
confidence: 73%
“…The demographic data of cases reported in this study were very similar to those reported among US travellers (60% women) [ 9 ]: considering the risk of severe pregnancy outcomes [ 10 ], it is expected that women of reproductive age, and particularly pregnant women, are more frequently tested. In our study, approximately 16% of infected women of reproductive age were pregnant, which is suggestive of increased testing in pregnant women.…”
Section: Discussionsupporting
confidence: 73%
“…Our results approximate the Global Travel Epidemiology Network analysis of pretravel consultations (13), in which 28% of 22,736 travelers planned trips to ZIKV-affected countries and >75% were of reproductive age. Another study retrospectively reviewed 46 patients for possible ZIKV infection and found 17% had laboratory evidence of infection (14).…”
supporting
confidence: 73%
“…Similarly, certain destination-specific illness risks have changed over the past 40 years. For example, the risk of acquiring an illness such as malaria, where national and global control programs successfully decreased disease prevalence, declined substantially, 26 while the risk of acquiring other emerging infectious diseases, such as Zika virus, 27 has simultaneously increased.…”
Section: Discussionmentioning
confidence: 99%